THE EFFECT OF EMOTIONAL INTELLIGENCE, POSITIVE EMOTIONS, NEGATIVE EMOTIONS ON ENTREPRENEURIAL INTEREST MEDIATED BY SELF-EFFICACY FOR VOCATIONAL SCHOOL STUDENTS - Ichsanudin; Mintasih Indriayu; Muhammad Sabandi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Entrepreneurial interest in vocational high school students is an important factor in preparing independent graduates who are ready to face the competitive world of work. However, various studies have shown that psychological aspects such as emotional intelligence, positive emotions, negative emotions, and self-efficacy are still less comprehensively explored. This study aims to analyze the influence of emotional intelligence, positive emotions, and negative emotions on entrepreneurial interest with self-efficacy as a mediating variable in grade XII students of SMK Negeri 1 Giritontro. The study used a quantitative approach with a survey technique on 187 respondents, while data analysis was carried out through Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The results showed that emotional intelligence and positive emotions had a significant positive effect on self-efficacy, while negative emotions had a significant negative effect. Self-efficacy was also shown to have a positive effect on entrepreneurial interest and mediated the relationship between the three predictor variables. These findings emphasize the importance of strengthening emotional regulation and self-efficacy in entrepreneurship learning in vocational high schools